A construção da demanda para o serviço de psicologia no contexto da atenção básica à saúde e o da promoção de saúde no município de Uberaba – MG - Cunha, Keila Rezende (2008)
Psychology has grown as an area of ​​activity in the public service, which raises the need for changes in the way of exercising it, in order to adapt it to the particularities of this context of practice, which differs from the private clinic due to socio-cultural and social characteristics. of its clientele. Thus, this work aimed to analyze how the demands for the psychology service have been understood // interpreted by psychologists and to analyze the concepts and actions of health promotion developed by psychologists in Basic Health Units in the city of Uberaba. to base the analysis we refer to the trajectory of psychology in the public service, the contextualization of psychology in primary health care (ABS) and the relationship between primary care and health promotion. The theoretical and methodological approach chosen was qualitative due to the possibility of understanding each professional in their uniqueness. Twenty-six psychologists who work in primary care were interviewed, most of them have more than ten years of training and practice private practice as an activity outside the public service. For data analysis, we selected two themes: demand and health promotion. Regarding demand, the survey participants reported that there was an increase in spontaneous demand and referrals made by other professionals. The waiting lines are part of the daily routine of the services and there is no question on the part of the professionals on how to face them. The main demands for the service are divided according to the phase of the life cycle and are distributed among children, learning problems; among adolescents, issues of intra-family relationships, drugs and those relevant to their stage of development; and in relation to adults, depression, anxiety and family relationships. In relation to health promotion, the participants reported that more preventive than promotion actions are developed; health concepts are related to the transmission of information / guidance on quality of life and prevention; the relationship established between psychology and promotion is primarily through individual interventions during consultations. Thus, the demand has been built from the perspective of professionals, making the dialogical relationship between user, service and professional impossible. The approach adopted to face the demand that has arisen is still based on an individual clinical model that excludes the potential of the community. The explanatory model of the health-disease process of these professionals remains based on a classic and Cartesian perspective that has no room for effective health promotion actions, since it is not fully understood by the professionals. We believe, therefore, that the difficulties encountered for a psychological practice in primary health care (ABS) must be understood from several dimensions: the training of the professional centered on the individual clinical model, different from what is expected from his performance in the context of ABS; the organization of the service that maintains this model and the absence of the practice of permanent education in services that contemplate this lapse in professional training; and, finally, the professional who takes an uncritical position in face of a reality not reflected during his education. In this sense, it is essential that there is a review in the curricula of training courses, an adjustment in the way of recording the actions of psychology, and the recognition, by the professional, of the need for change in their proposals and recognition of the user as a subject. And above all, we consider it important for psychologists to reflect on their identity in the public service and in primary care that enables the ethical and political positioning of professionals in the context of ABS. Keywords: Psychology; Basic health care; Demand; Health promotion.